Frosting modeling on a cold flat plate: Comparison of the different assumptions and impacts on frost growth predictions. (September 2016) - Brèque, Florent; Nemer, Maroun
Highlights: The equations used to model frost and the main different assumptions are presented. Models resulting from the different assumptions are compared to experimental data. The analysis helps understanding the different mechanisms involved in frosting. A suitable set of equations and assumptions is proposed for simple frost models. For advanced modeling requiring high precision, ways for improvement are pointed out. Abstract: Frost growth modeling based on heat and mass diffusion through a porous media is studied in this paper. First, the basic set of equations is established. Then, the main different assumptions used to handle this basic set are presented. Thus, different models, including models found in the literature, are developed. Simulation results from the models are compared to each other and to experimental data. Impacts of each assumption are analyzed. It appears that several assumptions have dramatic impacts on the predictions. Frost thicknesses can be tripled from one model to another one. The effects of the different assumptions are explained, and recommendations to select proper assumptions are made. It appears that simple and reliable frost growth models exist. Those models are particularly suitable for applications requiring low frost growth model complexity (system modeling for instance). On the other hand, the pathway to improve predictions is also pointed out.